2001
DOI: 10.1557/proc-671-m7.4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Post-CMP Cleaning

Abstract: We investigate the post-CMP cleaning process with a tribological approach. A cleaning process involves three components: brush, wafer/disk, fluid undergoing three-body sliding contact between the brush, wafer, and particles from slurry. Having this in mind, we investigated cleaning mechanisms through experimental measurement of friction force and analyzed the contact condition for particle removal. Our investigation leads to the conclusions that the cleaning process is a boundary to elastohydrodynamic lubricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…For example, H. Liang et al investigated the relationship between the particle removal by a PVA brush and frictional force and found that the CMP cleaning process was characterized by both boundary lubrication and the elastohydrodynamic lubrication phenomena caused by the constant contact between the PVA brush and the cleaning target. 1) However, even though friction is explained by the interactions between the contacting interfaces and viscoelastic properties, it is difficult to evaluate those interactions quantitatively. For example, Y.…”
mentioning
confidence: 99%
“…For example, H. Liang et al investigated the relationship between the particle removal by a PVA brush and frictional force and found that the CMP cleaning process was characterized by both boundary lubrication and the elastohydrodynamic lubrication phenomena caused by the constant contact between the PVA brush and the cleaning target. 1) However, even though friction is explained by the interactions between the contacting interfaces and viscoelastic properties, it is difficult to evaluate those interactions quantitatively. For example, Y.…”
mentioning
confidence: 99%